Pathological findings in a mouse model for Coxsackievirus A16 infection - Yuan, Teng Hooi; Kien, Chai Ong; Perera, David; Kum, Thong Wong (ASEAN Neurological Association (ASNA), Asian & Oceanian Association of Neurology (AOAN), and the Asian & Oceanian Child Neurology Association, 2015)
Coxsackievirus A16 (CV-A16) is the leading cause of hand-foot-mouth disease (HFMD), which usually presents as mild and self-limiting symptoms in young children. Rarely, CV-A16 has been reported to cause severe and fatal neurological complications but little is known about these complications. In the present study, 1-day and 7-day old mouse models of CV-A16 were developed using a clinical strain via subcutaneous inoculation. All infected mice exhibited clinical signs of infection, including reduced mobility, limb weakness and paralysis between 3 to 6 days post-infection. Pathologically, the main organs involved were the central nervous system (CNS), skeletal muscles and brown fat. In the CNS, viral antigens as demonstrated by immunohistochemistry, were localized mainly to neurons in the brain stem and spinal cord, suggesting that CV-A16 is neurotropic although inflammation is very mild. The skeletal muscles showed necrosis and myositis due to viral infection as evidenced by the dense viral antigens. Focal viral antigens were also detected in the brown fat. These preliminary pathological findings indicate that our mouse models can be further developed to be useful models for pathogenesis studies, and vaccine and anti-viral drug evaluation.